Green Innovation and its Impact on Cosmetic Accounting: Insights from Corporate Sustainability in Gulf Economies - Alazab, Hani Abdelhafez; Bawaneh, Ahmad Ali Salem; Alazab, Seleen Hani Abdel Hafez (International Review of Management and Marketing, 2026)
This research explores the interplay between green innovation, sustainability, and cosmetic accounting in GCC companies based on 938 firm-year observations (2010-2024). Using stakeholder and institutional theories, it suggests firms pursue green practices to boost legitimacy and preserve financial performance to meet stakeholders’ expectations. The findings are robust to controls for endogeneity, and to other measures of sustainability. Findings show the significant role of industry-based regulation on sustainability. The research shows green innovation has both positive and negative implications: driving environmental improvement but potentially facilitating "green washing". Governments must mandate uniform sustainability reporting, and companies need to embed sustainability into their strategies. The study is limited by differences in sustainability measures and geographical location, and offers opportunities for further research.